Comparison of tracheal diameter in non-brachycephalic versus brachycephalic dogs using manubrium and thoracic inlet tracheal indexes - Mostafa, Ayman A.; McCutcheon, Kaitlyn; Berry, Clifford R. (Frontiers in Veterinary Science, 2024)
IntroductionNarrowed tracheal lumen diameter (TLD) in dogs caused by congenital hypoplasia or acquired tracheal stenosis can result in adverse health effects. Standardized tracheal scores calculated from radiographic measurements have been used to assess tracheal diameter however comparisons have not been made to characterize differences in tracheal lumen among breeds.MethodsThe main objective of this study was to compare tracheal scores at three regions of the trachea among non-brachycephalic dogs, non-bulldog brachycephalic dogs, and bulldogs. Medical records and thoracic radiographs of clinically normal dogs were reviewed. The TLDs 79 of three different tracheal regions (caudal cervical, thoracic inlet, and intrathoracic) were standardized by the manubrium length (ML) and thoracic inlet distance (Ti-D) to calculate the manubrium and thoracic inlet tracheal indexes (M-TI and Ti-TI) at each region. Statistical analysis was used to analyze the differences in tracheal scores among the three breed populations.ResultsOverall, M-TI and Ti-TI varied significantly (p < 0.0001) at the three tracheal levels among the three breed populations. Bulldogs and non-bulldog brachycephalic breeds possessed lower (p < 0.016) M-TI and Ti-TI than non-brachycephalic breeds at the three tracheal regions, and bulldogs possessed the lowest M-TI and Ti-TI scores at all measured regions.ConclusionAveraged M-TIs <0.38, <0.34, <0.32 in non-brachycephalic, non-bulldog brachycephalic, and bulldog breeds, respectively, may indicate tracheal hypoplasia. Utilizing M-TI can be recommended for the assessment of canine TLD however further investigation in dogs with concurrent respiratory diseases is warranted.